Kahoot-based interactive game management in ipas learning to enhance students’ learning motivation - Yani Rahmawati; Endang Komara (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Learning in elementary schools is still dominated by conventional methods that make students passive and less motivated, especially in Ilmu Pengetahuan Alam dan Sosial (IPAS) subjects. This study aims to describe the application of Kahoot with the Plan–Do–Check-Act (PDCA) framework and analyze its influence on students' learning motivation. The study uses a phenomenological qualitative approach with the subjects of teachers and grade V students at SDN Leuwiorok and SDN Palasari, Sukabumi Regency. Data were obtained through participatory observation, in-depth interviews, and documentation, then analyzed with the Miles and Huberman model and tested for validity through triangulation of sources and methods. The results show that the integration of Kahoot in PDCA results in more systematic planning, the implementation of interactive learning, reflection-based evaluation, and continuous follow-up. Students showed increased enthusiasm, active participation, and motivation to learn compared to conventional methods. These findings confirm the novelty that Kahoot not only serves as an evaluation medium, but can also be integrated as an innovative, fun and supportive learning management instrument for 21st century skills.